THE REBELLION IN DONJI VASOJEVIĆI IN 1898 (Heritage, 2020)
AThe Serb population in Donji Vasojevići was all the more frequently exposed to attacks by Muslims and Arbanasi from Bihor, Rožaj and Rugova who had always mowed their meadows, looted their livestock, took away the crops and all their movable property. The Arbanasi from Rugova often attacked individual villages, and Turkish authorities in Berane did not want to protect them, but arrested individual leaders of Donji Vasojevići.In 1897 Arbanasi managed to kill several members of the Pantović family from Police (hamlet of Goražde). However, the Pantovićs did not forget this but rather took double revenge in May 1898. They first killed two Arbanasi from Rožaje, and three days later, two Rugovians, ox-cart men who were moving from Bijelo Polje to Berane. This served as an occasion for the Arbanasi and Muslim leaders to prepare a new and even stronger attack on the Serb population in Donji Vasojevići. According to an earlier agreement between the Rugovians, Rožajans and Bihorians, the attack on Donji Vasojevići began on May 31 in the villages on the right of the river Lim. During the first two days of the battle, the villages of Donji Vasojevići on the right side of the river Lim were burned: Luge, Petnjik, Dapsiće, Budimlje, the Polič villages, most of Donja Ržanica, Rovca, Kaludra and Zagorje. After receiving help of 3,000 Arnaut bashi-bazouk troops and two battalions of the standing Turkish army, on the fifth day of battles (June 4), the Turkish army launched actions on Serb villages on the left bank of the river Lim, as well as their sanctuary, The Tracts of Saint George Monastery /Djurdjevi Stupovi/. The soldiers planned to set fire to the Monastery and the school. Despite its numerical superiority and persistence, the enemy failed to achieve their goal. Through the heroic struggle, the detainees stopped their assaults, causing them great losses. The Arbanasi and the Turkish authorities who had helped them were terrified with this defeat, so they rushed and immediately the next day, June 7, asked the Serbs for peace, referring the request of the Sultan himself.The events in Donji Vasojevići worried Montenegro and Serbia. The Serbian MP in Constantinople, Stojan Novaković, was in constant contact with the Montenegrin MP M. Bakić and the Russian Consul Zinovjev. These are the three diplomats who mediated the most with the Sublime Port, thus contributing to replace the conflicts with diplomatic negotiations. The Serbian and Montenegrin governments and their authorities did their best to present the position of the Orthodox population in Donji Vasojevići to the world public.
Keywords: Donji Vasojevići, Serbs, Serbia, Montenegor, Porta, Serbian villages, Arbanasi, Rugovians, Rožajans and Bihorians